Experience of the patient regarding their safety in the hospital environment - Ana Cristina Pretto Báo; Cassiana Gil Prates; Marcelo Prado Amaral-Rosa; Diovane Ghignatti da Costa; João Lucas Campos de Oliveira; Simone Coelho Amestoy; Ana Maria Müller de Magalhães; Gisela Maria Schebella Souto de Moura (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to analyze the factors that can impact patients' experience concerning safety-related measures in the hospital setting. Methods: this qualitative, descriptive, and exploratory study was conducted with patients and their family members at a hospital in southern Brazil. Semi-structured interviews were carried out using the Critical Incident Technique between January and February 2022. The collected data underwent content analysis with the assistance of IRaMuTeQ software. Results: five patients, four family members, and three patient-family units participated in the study. The following categories emerged: "Patientprofessional interaction as a component of safe care," "Recognition of safety protocols in the patient's experience," and "Safe care and the challenges in hospital care." Conclusions: patient-professional interaction, communication, awareness of safety protocols, and the availability of the nursing team are factors that influence patients' experience regarding the safety of their care during hospitalization.